ptimasi Proses Pengolahan Bambu Petung menggunakan Ekstrak Nabati dan Kimia - Dwi Suheryanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Bamboo construction industry is very significant contribution to the foreign exchange and employment. Their products in addition to meet the needs of the local market, also exported to foreign countries. Problems are often found in industrial products produced bamboo is susceptible to damage from destructive insects, so it will degrade the quality of the product. The main material used is petung bamboo (Dendrocalamus asper), and substance use preservatives clicking processing plant leaf extract babadotan (Ageratum conyzoides Linn) and neem (Azadirachta indica A. Juss), as well as chemical preservatives borax-boric ( 2: 3). The purpose of this research is to improve the quality petung against destructive insects. The activities include, sample test, manufacture extract solution preservative plant from leaf babadotan, and neem by extraction with a ratio of 1::8, then boiled until the solution of the remaining 50%, the concentration of the use of 1:1, while the borax-boric ratio (2:3) using 50 g / l. Processing is done by boiling for 2 hours  and 4 hours, then the test sample testing moisture content, retention of preservative, and the value  of damage.The results of the observation showed initial moisture content petung average of 28.96%, the value of the optimal retention of borax-boric preservative occurs at boiling for 4 hours, that’s is 0.3693 g / cm3, using a solution of babadotan and neem leaf extract, respectively each of 0.117 g / cm3 and 0.109 g / cm3, under these conditions showed no damage petung against destructive insects.